2011
DOI: 10.1007/s11064-011-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Trisphosphate Receptor Subtype-Specific Regulation of Calcium Oscillations

Abstract: Oscillatory fluctuations in the cytosolic concentration of free calcium ions (Ca2+) are considered a ubiquitous mechanism for controlling multiple cellular processes. Inositol 1,4,5-trisphosphate (IP3) receptors (IP3R) are intracellular Ca2+ release channels that mediate Ca2+ release from endoplasmic reticulum (ER) Ca2+ stores. The three IP3R subtypes described so far exhibit differential structural, biophysical, and biochemical properties. Subtype specific regulation of IP3R by the endogenous modulators IP3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 108 publications
1
53
0
3
Order By: Relevance
“…In fact, the properties of Ca 2+ oscillation patterns depend on the relative expression levels of IP3R subtypes, probably because of their specific response to endogenous modulators, such as IP3, Ca 2+ and ATP. Pertaining to Ca 2+ oscillations, IP3R2 is required for robust, long-lasting, and regular Ca 2+ oscillations; IP3R1 mediates less regular Ca 2+ oscillations; and given that IP3R3 is the least sensitive to IP3 as well as to Ca 2+ it generates only monophasic Ca 2+ transients [37,54]. Contribution from all IP3R subtypes is likely necessary for the characteristics (frequency, amplitude, amount of liberated Ca 2+ , etc.)…”
Section: Functional Characterisation Of Internal Ca 2+ Stores and Thementioning
confidence: 99%
“…In fact, the properties of Ca 2+ oscillation patterns depend on the relative expression levels of IP3R subtypes, probably because of their specific response to endogenous modulators, such as IP3, Ca 2+ and ATP. Pertaining to Ca 2+ oscillations, IP3R2 is required for robust, long-lasting, and regular Ca 2+ oscillations; IP3R1 mediates less regular Ca 2+ oscillations; and given that IP3R3 is the least sensitive to IP3 as well as to Ca 2+ it generates only monophasic Ca 2+ transients [37,54]. Contribution from all IP3R subtypes is likely necessary for the characteristics (frequency, amplitude, amount of liberated Ca 2+ , etc.)…”
Section: Functional Characterisation Of Internal Ca 2+ Stores and Thementioning
confidence: 99%
“…2ϩ Signals-Previous studies have indicated that intracellular Ca 2ϩ fluctuations are generated in a subtype-specific manner (24,41,60). Although the mechanism underlying Ca 2ϩ oscillations is not clearly understood, the general consensus is that Ca 2ϩ oscillations may reflect the dynamic interplay between IP 3 binding, regulation by cytosolic and luminal Ca 2ϩ , as well as the availability of various modulators of IP 3 R (41).…”
Section: Subunit Composition Influences the Characteristics Of Cytosomentioning
confidence: 99%
“…Although the mechanism underlying Ca 2ϩ oscillations is not clearly understood, the general consensus is that Ca 2ϩ oscillations may reflect the dynamic interplay between IP 3 binding, regulation by cytosolic and luminal Ca 2ϩ , as well as the availability of various modulators of IP 3 R (41). Given isoform-specific regulation, the coordinated effect of these factors would obviously be influenced by the complement of IP 3 R subtypes expressed in a particular cell (60). For example, studies using DT40 cells genetically manipulated to express one IP 3 R subtype in isolation have indicated that IP 3 R1 generates largely monophasic Ca 2ϩ peaks with some low amplitude infrequent fluctuations.…”
Section: Subunit Composition Influences the Characteristics Of Cytosomentioning
confidence: 99%
“…However, this perception arose from the use of the rat RIN m5F b-cell line, which is enriched in this receptor and was reinforced by subsequent studies on primary rat b-cells; these had the same dominance as the type 3 receptor (Lee et al, 1999). However, in mouse pancreatic b-cells, the type 1 is as abundant as type 3 (Lee and Laychock, 2001 (Zhang et al, 2011).…”
Section: +mentioning
confidence: 99%